1999
DOI: 10.1002/hep.510290510
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Rat Hepatocyte Protein Kinase C β Isoenzymes by the Lipid Peroxidation Product 4–Hydroxy–2,3–Nonenal: A Signaling Pathway to Modulate Vesicular Transport of Glycoproteins

Abstract: A major aldehydic end product of the peroxidation of arachidonic acid, 4-hydroxy-2,3-nonenal (HNE), has recently been considered for its potential involvement in a variety of cell functions. Here we report on the differential regulation of rat hepatocyte protein kinase C (PKC) isoforms by concentrations of HNE actually detectable in specific biological fluids or tissues. PKC ␤I and, to a much greater extent, PKC ␤II activities were markedly increased by 0.1 mol/L HNE (final concentration in cell medium) wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 49 publications
7
44
0
Order By: Relevance
“…This finding was supported by other reports, which, either by using PKC-βI and βII inhibitor GO6976, or by directly measuring kinase activity, demonstrated that these two PKC isozymes were activated by < 1 μM HNE (200). In contrast to PKC-β, the novel PKC-δ activity was inhibited by 0.1 μM HNE but increased by 1-10 μM HNE (199,200) . Numazawa also reported that HNE-mediated HO-1 induction was completely abrogated by dominant-negative expression of atypical PKC-ι (201), suggesting that HNE may also activate PKC-ι.…”
Section: A Activation Of Protein Kinase C By Hnesupporting
confidence: 86%
See 1 more Smart Citation
“…This finding was supported by other reports, which, either by using PKC-βI and βII inhibitor GO6976, or by directly measuring kinase activity, demonstrated that these two PKC isozymes were activated by < 1 μM HNE (200). In contrast to PKC-β, the novel PKC-δ activity was inhibited by 0.1 μM HNE but increased by 1-10 μM HNE (199,200) . Numazawa also reported that HNE-mediated HO-1 induction was completely abrogated by dominant-negative expression of atypical PKC-ι (201), suggesting that HNE may also activate PKC-ι.…”
Section: A Activation Of Protein Kinase C By Hnesupporting
confidence: 86%
“…In rat hepatocyte, they demonstrated that PKC-βI and βII were activated by HNE at concentrations 0.1-1 μM, while they were inhibited when HNE concentration was higher than 1μM (1-10 μM) (199). This finding was supported by other reports, which, either by using PKC-βI and βII inhibitor GO6976, or by directly measuring kinase activity, demonstrated that these two PKC isozymes were activated by < 1 μM HNE (200).…”
Section: A Activation Of Protein Kinase C By Hnesupporting
confidence: 63%
“…Thus, HNE can influence a large set of fundamental cellular processes including proliferation, cell cycle events, and apoptosis and can modulate the expression of numerous genes. This is consistent with the reported effect of HNE on many genes including c-myc, AKT, PKC, TGFβ, ASK1, JNK, Nrf2, integrins, connexins, ERK pathway genes, aldose reductase, glycogen synthase kinase, gamma-glutamyl transferase (GGT), adenylate cyclase, RalBP1, and heat shock proteins among others [3,13,25,45,52,57,65,74]. The underlying mechanisms for such a global effect of HNE on gene expression are largely unclear.…”
Section: Hne and Transcription Repressors/factorssupporting
confidence: 80%
“…Triggers an epidermal growth factor receptor for growth inhibition [64] Rat hepatocytes Regulation of PKC beta isozymes [65] HeLa cells Affects expression of c-fos proto-oncogene and proliferation [66] Rat cerebrocortical neurons Inhibition of muscarinic acetylcholine and metabotropic glutamate receptor-mediated signaling [67] Rat hepatocytes Triggers Ca 2+ influx [68] Human cerebral arteries Induces relaxation [69] Neutrophils Stimulation of chemotaxis [70] Rat live plasma membrane Activation of adenylate cyclase [71] Hepatic tissues Activation of phospholipase c [72] Hepatoma cells Stimulation of heat shock proteins [73] K562 cells Inhibition of C-myc [74] HL60 cells Cell cycle progression and expression of differentiationassociated antigens [75] Macrophages Activates transcription factor AP-1 [76] Free Radic Biol Med. Author manuscript; available in PMC 2009 July 15.…”
Section: Model System Observed Effect(s); Ref Given In Parenthesesmentioning
confidence: 99%
“…16 HNE interaction with key amino acids of catalytic sites could explain the inhibition of these enzymes. 16 Although HNE-dependent protein modulation relies mainly on post-translational modifications, the regulation of gene expression by HNE has also been described notably by modulation of NF-kB (nuclear factor-kappa B) and AP-1 (activator protein 1) transcription factors, which are related to Figure 1 Reactivity of HNE. Here are represented the potential reactions of HNE on the hydroxyl, carbonyl and double bond groups.…”
Section: -Hydroxynonenal: a Highly Reactive Product Of Lipoperoxidationmentioning
confidence: 99%